INFLUENCE OF STOCKING DENSITY ON GROWTH PERFORMANCE TRAITS, BLOOD CHEMISTRY AND THE EXPRESSION OF HSP70 AND IGF-I GENES IN NEW ZEALAND WHITE RABBITS - Khairy M. El-Bayoumi; Tamer M. Abdel-Hamid; Mahmoud S. El-Tarabany; Wafaa R.I.A. Sherief (Slovenian Veterinary Research, 2018)
This research was done to mainfest the effect of stocking density on growth performance traits, blood chemistry and the expression of heat shock protein (HSP) 70 and insulin-like growth factor I (IGF-I) genes in growing New Zealand White rabbits. A total of 75 rabbits at weaning (35 days of age) were randomly assigned into three stocking densities of 12, 20 and 28 rabbits/m2 from weaning until 13 weeks of age. Rabbits housed at 28 rabbits/m2 had the lowest feed intake, live body weight and body weight gain, but they had the highest feed to gain ratio when compared with the lower densities. Moreover, rabbits housed at 28 rabbits/m2 showed the highest serum creatinine, glucose and cortisol levels compared with rabbits housed at 20 and 12 rabbits/m2. High stocking density up-regulated the expression of HSP70 gene when compared with the lower densities. Meanwhile, IGF-I mRNA expression was significantly reduced in the rabbits housed at 28 rabbits/m2. In conclusion, high stocking densities (28 rabbit/m2) had negative impacts on growth performance traits and the stress-related parameters (serum glucose, cortisol and creatinine). Moreover, the expression of HSP70 gene was increased, with a remarkable reduction in IGF-I gene expression in the high stocking group.